Fenomena Pernikahan Antar Anak Kiai di Indonesia Perspektif Fikih Empat Mazhab - Almiyati, Almiyati; Hidayat, Yayat; Eka, Eka (AL-MASHALIH (Journal of Islamic Law), 2025)
Marriages among religious figures, particularly within the circle of kiai (Islamic scholars), represent a significant phenomenon in Indonesian society. This practice aims to preserve the pesantren lineage or family heritage, while also being regarded as an effort to ensure compatibility or equality (kafa’ah) in social and religious contexts. This study explores the underlying social and religious dynamics of the phenomenon and its impact on social structures. Lineage (nasab) becomes a primary consideration in spouse selection among kyai. The objectives of this research are to examine the phenomenon of marriage among the children of kiai in Indonesia and to analyze it from the perspective of Islamic law, specifically through the lens of the four major schools of fikh. This study employs a qualitative method with a library research approach. Data were collected through documentation derived from books and journal articles. The findings of this study are twofold. First, marriages among the children of kiai in Indonesia are indeed a long-standing tradition within the pesantren elite, passed down from generation to generation and often arranged by parents. The purpose of such marriages is to strengthen religious commitment, social networks, and political ties between pesantren or ulama families. Society views marriage among kiai descendants as a form of propriety or kafa’ah. Although many marriages are arranged from an early age, there is no coercion in the process, as consent and willingness remain essential prerequisites for marriage. Second, from the perspective of Islamic law according to the four schools of fikh, scholars differ in their opinions regarding the legal status of kafa’ah. The Hanafi school considers kafa’ah non-obligatory but important; the Maliki school regards it as recommended (sunnah); the Shafi’i school stipulates kafa’ah as a requirement set by the guardian (wali); and the Hanbali school also deems it a requirement. Therefore, marriage among the children of kiai, according to scholars of the four schools, is permissible as it fulfills the concept of kafa’ah and aligns with Islamic principles.